Verifikasi Metode Uji Nitrit (NO2-N) pada Air Sungai Sesuai SNI 06.6989.9-2004 - Angle Cendriani; Ali Amran (Lembaga Yasin AlSys, 2026)
Although water quality monitoring has been widely conducted, studies that specifically examine the verification of nitrite (NO₂-N) test methods in environmental laboratories remain limited. This study aimed to verify the nitrite test method in river water based on SNI 06.6989.9-2004 using a UV-Vis spectrophotometer at the Water Quality Laboratory of BSPJI Padang. This study used an experimental quantitative approach through laboratory testing, which included the preparation of standard solutions, construction of a calibration curve, and absorbance measurement at a wavelength of 543 nm. Data were analyzed using linear regression to evaluate method performance parameters, including linearity, precision, and limit of detection. The results showed a strong linear relationship between concentration and absorbance, with a slope value of 3.4324 and an intercept value of 0.0039, indicating good method linearity. This method also demonstrated precision and sensitivity that met the criteria for nitrite analysis in river water. These findings confirm that the SNI 06.6989.9-2004 method can be reliably applied at the Water Quality Laboratory of BSPJI Padang. This study contributes to strengthening the verification of analytical methods in environmental monitoring and supports the implementation of standard procedures in water quality analysis.